The "Things of Greater Importance" Bernard of Clairvaux's "Apologia" and the Medieval Attitude Toward Art - Rudolph, Conrad (University of Pennsylvania Press, 2016)
The "Things of Greater Importance" provides a close look into the social and cultural context of medieval art, primarily as expressed in Bernard of Clairvaux's Apologia, the central document in the greatest artistic controversy to occur in the West prior to the Reformation and the most important source we have for understanding medieval attitudes toward art. Bernard wrote the Apologia during the medieval efflorescence of monumental sculpture and stained glass, of advanced architecture, of pilgrimage art, of high Romanesque, and of the origins of Gothic art. Rudolph places the Apologia, traditionally seen as a condemnation either of all religious art or of all monastic art, in a broader context, using it to explore the role of art in medieval society. He shows that Bernard was interested in the impact of art on contemporary monasticism in a more complex way than previously believed. The book offers the most thorough study available of the theoretical basis of medieval art as it functioned in society; and its implications for the art of both the Romanesque and Gothic periods, which were spanned by Bernard's life, are significant